2022
DOI: 10.3389/fnins.2022.892768
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Interruption by Intron Variants in CSNK2B Causes Poirier–Bienvenu Neurodevelopmental Syndrome: A Focus on Genotype–Phenotype Correlations

Abstract: CSNK2B has recently been identified as the causative gene for Poirier–Bienvenu neurodevelopmental syndrome (POBINDS). POBINDS is a rare neurodevelopmental disorder characterized by early-onset epilepsy, developmental delay, hypotonia, and dysmorphism. Limited by the scarcity of patients, the genotype–phenotype correlations in POBINDS are still unclear. In the present study, we describe the clinical and genetic characteristics of eight individuals with POBINDS, most of whom suffered developmental delay, general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…CK2β regulates the substrate specific targeting of the catalytic subunit (Lettieri et al, 2019) and together forms a complete CK2 protein kinase structure (Yang et al, 2021). Zhang et al (2022) and Li et al (2019) suggested that variants in zinc finger structural domain cause a milder POBINDS phenotype and that epilepsy is more easily controlled. In contrast, Ballardin et al (2022) suggested that variants in the zinc finger and/or C-terminal structural domains appear to have a more severe phenotype than variants in the N-terminal region in patients with POBINDS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CK2β regulates the substrate specific targeting of the catalytic subunit (Lettieri et al, 2019) and together forms a complete CK2 protein kinase structure (Yang et al, 2021). Zhang et al (2022) and Li et al (2019) suggested that variants in zinc finger structural domain cause a milder POBINDS phenotype and that epilepsy is more easily controlled. In contrast, Ballardin et al (2022) suggested that variants in the zinc finger and/or C-terminal structural domains appear to have a more severe phenotype than variants in the N-terminal region in patients with POBINDS.…”
Section: Discussionmentioning
confidence: 99%
“…(2017), about 81 cases currently reported (including the present case, searched in PubMed), is a rare autosomal dominant neurological disorder caused by heterozygous variants of CSNK2B . POBINDS mostly characterized by different degrees of early onset epilepsy (including GTC, myoclonic seizures, febrile epilepsy, partial‐onset epilepsy, and so on), ID, DD and hypotonia (Di Stazio et al., 2023; Zhang et al., 2022). Some patients have facial dysmorphism, autistic features, learning disabilities (LD), attention deficits, etc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations